How useful are virtual fracture clinics?: a systematic review. (1st November 2020) - Khan, Shehzaad A.; Asokan, Ajay; Handford, Charles; Logan, Peter; Moores, Thomas
Abstract : Background: Due to the overwhelming demand for trauma services, resulting from increasing emergency department attendances over the past decade, virtual fracture clinics (VFCs) have become the fashion to keep up with the demand and help comply with the BOA Standards for Trauma and Orthopaedics (BOAST) guidelines. In this article, we perform a systematic review asking, "How useful are VFCs?", and what injuries and conditions can be treated safely and effectively, to help decrease patient face to face consultations. Our primary outcomes were patient satisfaction, clinical efficiency and cost analysis, and clinical outcomes. Methods: We performed a systematic literature search of all papers pertaining to VFCs, using the search engines PubMed, MEDLINE, and the Cochrane Database, according to the Preferred Reporting Items for Systematic review and Meta-Analysis (PRISMA) checklist. Searches were carried out and screened by two authors, with final study eligibility confirmed by the senior author. Results: In total, 21 records were relevant to our research question. Six orthopaedic injuries were identified as suitable for VFC review, with a further four discussed in detail. A reduction of face to face appointments of up to 50% was reported with greater compliance to BOAST guidelines (46.4%) and cost saving (up to £212, 000). Conclusions: This systematic review demonstrates that the VFC model can help deliver a safe, more cost-effective, and more efficient arm of the trauma service to patients. Cite this article: Bone Joint Open 2020;1-11:683–690.